Table of Content - - (Journal of natural sciences, life and applied sciences, 2025)
:Table of Content • Utilization of the Byproduct from Phonolite Rock Exploitation in the Production of Ceramic Bodies Dr. Halima Al-Shaibani Abusriwil, Ms. Numidia Fouad Ftis • Monitoring Sand Encroachment on Highways in the Qassim Region Using Remote Sensing and Geographic Information Systems Ms. Fidaa Sulaiman Al-Omar, Prof. Mohammed Ibrahim Al-Dughairi • Evolution of the Lower Valley of Oued Za during the Quaternary (Northeastern Morocco) Dr. BENHAMED Abderrahim, PES. SBAI Abdelkader • Effectiveness of Urban Parks in Reducing Surface Temperatures in Riyadh City Using Remote Sensing and Geographic Information Systems Dr. Haya Falah Al-Shahrani